Diurnal variations of the ionospheric electron density height profiles over Irkutsk: Comparison of the incoherent scatter radar measurements, GSM TIP simulations and IRI predictions. Issue 2 (15th July 2017) - Zherebtsov, G.A.; Ratovsky, K.G.; Klimenko, M.V.; Klimenko, V.V.; Medvedev, A.V.; Alsatkin, S.S.; Oinats, A.V.; Lukianova, R.Yu.
Abstract: The long-duration continuous Irkutsk incoherent scatter radar (ISR) measurements allowed us to obtain the monthly averaged height-diurnal variations of the electron density in the 180–600 km altitudinal range for 4 four seasons (winter, spring, summer, autumn) and for two solar activity levels (low and moderate). Considering these electron density variations as "quiet ionosphere patterns" we compared them with the Global Self-consistent Model of the Thermosphere, Ionosphere and Protonosphere (GSM TIP) simulations and the International Reference Ionosphere (IRI) predictions. It was found that some observational features revealed from the ISR measurements are reproduced nicely by both the theoretical and empirical models, and some features agree better with the GSM TIP than with IRI. None of the models is able to reproduce a detailed multi-peak behavior of the electron density observed by ISR at ∼300 km and above for the spring and autumn under low solar activity, while for the spring the GSM TIP tends to reproduce the morning and daytime peaks at the same local times as they are seen from the ISR observations.